A Comprehensive Study on Blockchain Technology - Sunil Kumar Dewangan, Astha Pathak, Vaishali Raheja, Harshal Shende, Chaitanya Verma, Sambhav Jain (Mathematical Statistician and Engineering Applications, 2023)
Blockchain can be demarcated as a shared or distributed, immutable archive that provides the process of recording transactions. This innovation has given an important turn to the business environment. Keeping record of facts and details about transactions are vital part. Generally, those fact and data are passed through a trusted third party which increases both time and cost on business. Instead of this lengthy process Blockchain provides much faster process for transaction, which helps in saving money and time without the need of any third party. It assures data clarity, integrity and security as it is cannot be tampered. Blockchains are famous for their important role in cryptocurrency systems, like Bitcoin. Blockchain technology also has some other applications in healthcare, Business management, supply chains, banking and Finance. The impartial of this paper is to study about what blockchain technology actually is, how does it work and its various underlying features and applications.